Cytologic and Clinical Evaluation of Human Papillomavirus in Women Underwent Routine Gynecologic Examination - Öz, Zehra Safi; Demirezen, Şayeste; Mocan Kuzey, Gamze; Beksaç, Mehmet Sinan; Ustaçelebi, Şemsettin (Gynecology Obstetrics & Reproductive Medicine, 2009)
OBJECTIVE: To determine the frequency of Human Papillomavirus infection in routine gynecologic examination and to detect whether there is a relationship between the presence of Human Papilloma Virus and cytologic and gynecological findings. STUDY DESIGN: Four hundred women applying to Gynecology outpatient clinic for routine gynecologic examination were included. Conventional Pap smears of 400 patients were stained by Papanicolaou technique and examined cytologically. HPV DNA was detected by in-house PCR . Also HPV positive samples were evaluated for HPV 16 and 18 by same method. RESULTS: Eleven (2.75%) of 400 women were HPV DNA (+). Two of which were type 16 and 18 and one of which was type 18. Nuclear membrane irregularity, hyperchromatism, koilocytotic cell, vacuolisation and post partum period corralated with HPV infection (p <0.05). CONCLUSION: Pap smear examination is a value of detection of cellular changes belonging Human Papillomavirus and if in this examination it is need to, these patients refer to Human Papillomavirus DNA screening it would be more cost effective.